Asparagine in plums detected by CEST–MRI. (15th February 2015) - Podda, Rachele; Delli Castelli, Daniela; Digilio, Giuseppe; Gullino, Maria Lodovica; Aime, Silvio
Highlights: CEST–MRI technique is applied for the first time in fruits. Saturation transfer (ST) change can be associated to pH variation during ripening. ST of amide protons from Asparagine can be followed at 1T scanner. Abstract: Magnetic resonance imaging (MRI) relies on the topological distribution of the intense water NMR signal and may be used to report about changes in the internal structures of fruits associated to ripening, storing, pathogen infection. Herein the use of CEST–MRI (chemical exchange saturation transfer) is introduced to show that in addition to structural information, insights into the presence in the fruits of specific chemicals may be gained. Asparagine is present in plums at relatively high concentration (≈10–20 mM) and owns two amide protons (at 2.1 and 2.8 ppm down field from water) in slow exchange with water protons. By irradiating the amide resonances with a proper rf-field it is possible to transfer saturated magnetization to the "bulk" water signal. The attained change in signal intensity reflects the extent of prototropic exchange between amide and water protons that is modulated by the local pH.